2023
DOI: 10.3389/fonc.2023.1105728
|View full text |Cite
|
Sign up to set email alerts
|

Is percutaneous drainage better than endoscopic drainage in the management of patients with malignant obstructive jaundice? A meta-analysis of RCTs

Abstract: To compare the safety and efficacy of endoscopic retrograde cholangiopancreatography (ERCP) and percutaneous transhepatic cholangial drainage (PTCD) in the treatment of malignant obstructive jaundice, a systematic review and meta-analysis of published studies was undertaken to assess the differences between the two procedures in terms of efficacy and safety. From November 2000 to November 2022, the Embase, PubMed, MEDLINE, and Cochrane databases were searched for randomized controlled trials (RCTs) on the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
1
Order By: Relevance
“…Some scholars have also reported that the incidence of postoperative complication rates is as high as 30% to 50% for PTCD, compared to only about 5% for ERCP ( 38 ). The results of the meta-analysis showed that although the overall complication rate was higher in the PTCD group than in the ERCP group, it was not statistically significant, which is inconsistent with the results of some previous studies ( 39 , 40 ). It may be due to the uneven grouping of some studies, which led to a bias towards patients with high levels of obstruction.…”
Section: Discussioncontrasting
confidence: 95%
“…Some scholars have also reported that the incidence of postoperative complication rates is as high as 30% to 50% for PTCD, compared to only about 5% for ERCP ( 38 ). The results of the meta-analysis showed that although the overall complication rate was higher in the PTCD group than in the ERCP group, it was not statistically significant, which is inconsistent with the results of some previous studies ( 39 , 40 ). It may be due to the uneven grouping of some studies, which led to a bias towards patients with high levels of obstruction.…”
Section: Discussioncontrasting
confidence: 95%